2020
DOI: 10.1249/mss.0000000000002447
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Muscle Recovery in Baseball Pitchers Using Phase Change Material Cooling

Abstract: The purpose of this study was to document recovery following a pitching performance and determine if prolonged post-game phase change material (PCM) cooling of the shoulder and forearm accelerates recovery. Methods: Strength, soreness and serum creatine kinase (CK) activity were assessed prior to, and on the two days following pitching performances in 16 college pitchers. Pitchers were randomized to receive either post-game PCM cooling packs on the shoulder and forearm, or no cooling (control). PCM packs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…A central effect from local 15 • C PCM cooling was since confirmed by the reduction in core temperature and increase in heart rate variability evident during PCM treatment in individuals at rest (Kwiecien et al, 2019). These findings suggested that prolonged PCM cooling delivered a systemic, and not just a local effect; and might explain, in part, the accelerated recovery evident from PCM cooling following eccentric exercise (Kwiecien et al, 2020a), soccer match play (Clifford et al, 2018;Brownstein et al, 2019) and baseball pitching (Mullaney et al, 2020). However, the central effect occurring from PCM cooling remains to be directly elucidated in individuals following exercise.…”
Section: Future Directionsmentioning
confidence: 89%
See 4 more Smart Citations
“…A central effect from local 15 • C PCM cooling was since confirmed by the reduction in core temperature and increase in heart rate variability evident during PCM treatment in individuals at rest (Kwiecien et al, 2019). These findings suggested that prolonged PCM cooling delivered a systemic, and not just a local effect; and might explain, in part, the accelerated recovery evident from PCM cooling following eccentric exercise (Kwiecien et al, 2020a), soccer match play (Clifford et al, 2018;Brownstein et al, 2019) and baseball pitching (Mullaney et al, 2020). However, the central effect occurring from PCM cooling remains to be directly elucidated in individuals following exercise.…”
Section: Future Directionsmentioning
confidence: 89%
“…Importantly, the protection provided by the PCM cooling after an initial bout of eccentric exercise did not interfere with the repeated bout effect, whereby an initial bout confers an adaptive protective effect for a subsequent bout of damaging exercise (Kwiecien et al, 2020a). Similarly, 3 h of 15 • C PCM cooling has also been shown to accelerate recovery of quadriceps strength following soccer match play (Clifford et al, 2018;Brownstein et al, 2019; Table 1) and shoulder internal rotation strength and grip strength following baseball pitching (Mullaney et al, 2020; Table 1). Alleviating strength loss at a rate faster than normal could allow athletes to be better prepared for subsequent performance, giving them a competitive advantage over the opposition.…”
Section: Evidencementioning
confidence: 98%
See 3 more Smart Citations